PERTANGGUNGJAWABAN KEPALA DAERAH ATAS PENYALAHGUNAAN DANA TRANSFER KE DAERAH: TANGGUNG JAWAB HUKUM DAN POLITIK - M. Khairu Mamnun; W. Riawan Tjandra (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2025)
This paper examines the complexity of regional heads' accountability for the misuse of Intergovernmental Fiscal Transfers (TKD) within Indonesia's fiscal decentralization framework. Although TKD is intended to support equitable development and improve welfare, it is often misappropriated by regional leaders at various levels. Employing a normative juridical method with literature review and case study approaches, this study reveals that misuse of TKD is not only a legal violation but also reflects structural weaknesses in fiscal and political oversight systems. Legally, accountability is enforced through criminal and administrative instruments involving the Corruption Eradication Commission (KPK), the Police, the Attorney General’s Office, and the Audit Board (BPK). Politically, mechanisms such as accountability reports to local parliaments (LKPJ), the right of inquiry, and public opinion play roles in supervising regional leaders. However, inadequate human resources, political interference, permissive culture, and poor inter-agency coordination hinder effective accountability. Therefore, an integrated strategy is required—encompassing digitalization of regional finance, strengthened oversight, regulatory reform, and public participation—to build a transparent and accountable fiscal governance system.